Repellency and toxicity of long-lasting insecticide-treated bed nets (LLINs) to bed bugs. - Christopher C Hayes; Coby Schal (PLoS ONE)
Vector control is essential for eliminating malaria, a vector-borne parasitic disease responsible for over half a million deaths annually. Success of vector control programs hinges on community acceptance of products like long-lasting insecticide-treated nets (LLINs). Communities in malaria-endemic regions often link LLIN efficacy to their ability to control indoor pests such as bed bugs (Cimex lectularius L. and Cimex hemipterus (F.)) (Hemiptera: Cimicidae). Despite this, little is known about the potential repellent effects and toxicity of LLINs to bed bugs. Herein, we demonstrate for the first time that commonly deployed LLINs lack olfactory and contact-based repellency to host-seeking C. lectularius from both insecticide-susceptible and insecticide-resistant populations. One LLIN (PermaNet Dual) was significantly attractive to both populations when exposed olfactorily, but not in contact assays, highlighting the complexity of bed bug-LLIN interactions. The insecticide resistant bed bugs experienced low mortality in 4 d of continuous exposure to LLINs. These results suggest that LLINs would likely not repel or eliminate bed bug infestations in malaria-endemic communities, further selecting for insecticide resistance and potentially disrupting vector control programs.